Prevalence, Risk Factors, Lung Function, and Associated Comorbidities of Adult Preserved Ratio Impaired Spirometry: A Meta‐Analysis - Haoyu Wang; Ruiyuan Yang; Dan Liu; Weimin Li (MedComm)
ABSTRACT It is demonstrated that preserved ratio impaired spirometry (PRISm) is associated with chronic obstructive pulmonary disease development and mortality. However, comprehensive evidence on its prevalence, risk factors, lung function, and comorbidities is ambiguous. We searched for relevant studies from Medline, Web of Science, Embase, and Scopus up to March 26, 2024, and conducted a meta‐analysis based on PRISMA 2020 to merge the results of eligible studies to reveal the prevalence, risk factors, lung function, and associated comorbidities in PRISm population. Thirty‐two studies involving 1,196,856 participants were included. The prevalence of PRISm was 11% (95%CI: 10–13%), with decreased forced vital capacity (FVC) (L) (MD: −0.78, 95%CI: −0.90 to −0.66) and FVC% predicted (MD: −24.74, 95%CI: −26.33 to −23.16). Older age, high body mass index, current or ever smoking, and low education were positively associated with PRISm, while cardiovascular and endocrine comorbidities were common in patients with PRISm. The prevalence of PRISm is high in general population, with multiple risk factors, reduced lung function, and increased comorbidities. Therefore, clinicians should raise more concerns regarding this population to benefit them.